Implementation of the New Normal Order Policy in Places of Worship During the Covid-19 Pandemic in the Ogan Ilir District - Zailani Surya Marpaung; Imelda Imelda; Tuty Khairunnisa (Kolaborasi : Jurnal Administrasi Publik, 2022)
This study aims to determine what factors influence the successful implementation of the new normal order policy in places of worship during the COVID-19 pandemic in the Ogan Ilir Regency. The policy implementation model used in this study is a Top-down using Edward III's theory which consists of communication variables, resources, dispositions, and bureaucratic structure. The research method used in this study is qualitative and quantitative (mixed methods) with data collection techniques, documentation, observation, interviews, and distributing questionnaires to visitors, mosque congregations, and the mosque's board of directors. The results of the study indicate that the implementor has understood the content and objectives of the policy, permits the application of the policy through direct communication, and appeals to comply with health protocols through direct socialization and indirect socialization. mosque management is divided into two managements, namely official management and executive management. Facilities and infrastructure to support policy implementation are also very adequate. The absence of problems during the implementation of the new normal order policy can be seen from the observance of the health protocol facilities provided by the mosque management. The response of visitors and congregations to the implementation of the new normal order policy shows that visitors and congregations can comply with these policies while still prioritizing mental health and safety. Although the status of several mosques is classified as waqf mosques, they have an organizational structure for the COVID-19 volunteer post which greatly assists the implementation of the policy to avoid the spread of the Coronavirus disease (COVID-19) virus.